DISKURSUS KONTEMPORER TENTANG PENDIDIKAN ISLAM: DIKOTOMI, ISLAMISASI DAN INTEGRASI ILMU PENGETAHUAN SERTA DAMPAKNYA BAGI PENDIDIKAN ISLAM - Muhamad Yahya (STAI Darul Quran Payakumbuh, 2016)
The case of dichotomy, Islamization, and integration of knowledge is a part of the education movement. This condition cannot be separated from the phenomenal background which occurs in the history of knowledge development. The emergence of ideas from Islamic education figures through Islamization and integration of knowledge is the answer to the problem of dichotomy which gives the bad effects toward Islamic education development. This matter will be the responsibility of an educator as the agent who develops the learning process and interacts with the students educationally.